Combating COVID-19 infodemic in Nigerian rural communities: The imperatives of Traditional Communication Systems - Lucas, Joseph M; Targema, Tordue Simon; Jibril, Abubakar; Sambo, Elkanah Obadiah; Istifanus, Bako Ali (UI Scholars Hub, 2020)
Since the outbreak of COVID-19 in December 2019, substantial attention has been devoted to combating the infodemic that has come to characterize it with the potential to prevent its effective containment. This is undoubtedly a very difficult task, especially in Nigerian rural communities that are characterized by severe lack of the requisite facilities to access information on modern media platforms, compounded by high illiteracy and poverty rates. This study presents a case for the utilization of people-oriented, traditional communication systems in combatting the infodemic at the grassroots level. It contends that, given the peculiarities of the country’s rural settlements, traditional communication systems present suitable alternatives that could be harnessed and leveraged upon to carry everyone along in the fight against the pandemic. Using data from secondary sources, the study argues that the fight against COVID-19 infodemic can be more effective if stakeholders recognize and optimize the opportunities offered by traditional communication systems and channel them towards mobilizing and sensitizing rural dwellers to disregard the myriad conspiracy theories and myths about the pandemic, and instead adopt positive behaviors that would help to curtail its spread. This will go a long way in filling the information gap that exists at the grassroots and more effectively help contain the pandemic. To achieve this, the study recommends the need for a robust health intelligentsia to be trained and equipped with skills and competencies in using these communication channels for effective mobilization and sensitization of the people at the grassroots.